The Effectiveness of Mobile App-Based Blended Learning on Students' Cognitive and Affective Competencies in Physical Education - Edward Keliat; Alan Alfiansyah Putra Karo Karo; Dicky Hendrawan (Journal Of Sport Education (JOPE), 2025)
The development of information and communication technology has had a significant impact on the world of education, including in the process of physical education learning. Learning, which was previously only done conventionally, has now shifted towards digitization and the use of application-based technology. This study aims to examine the effectiveness of mobile application-based blended learning in improving students' cognitive and affective competencies in physical education. The method used is a quasi-experiment with a pre-test and post-test control group design. The research subjects consisted of 60 high school students divided into two groups, namely the experimental group (n=30) who used mobile application-based blended learning and the control group (n=30) who used conventional learning. The results showed that the experimental group experienced an increase in cognitive scores from 56.4 to 82.7 and affective scores from 60.1 to 85.3. Meanwhile, the control group experienced an increase in cognitive scores from 55.8 to 69.4 and affective scores from 59.7 to 70.2. The t-test results showed a significant difference between the two groups (p < 0.05). This study concluded that mobile application-based blended learning is effective in improving students' cognitive and affective competencies.